Mother’s education and children’s nutrition outcomes in Burkina Faso: Is there a strong causal relationship? - Maiga, Eugenie (International Food Policy Research Institute, 2015)
This paper examines the relationship between mothers’ education and children’s nutrition outcomes, specifically child stunting (low height for age) and wasting (low weight for height), using data from the 2010 Demographic and Health Survey. Pathways through which mothers’ education impacts children’s nutrition outcomes are investigated, as are threshold effects of maternal education. We employ instrumental variable methods to account for the potential endogeneity of mother’s education, mother’s health knowledge, mother’s bargaining power, and household wealth; none of these variables appear endogenous so we then use fixed effects OLS regressions. The findings show that a mother’s education has a positive and significant effect on her children’s Height-for-Age Z score; no statistically significant impact on Weight-for-Height Z score was found. Mother’s health knowledge, mother’s bargaining power, and household wealth are the pathways through which maternal education affects children’s health. The impact of maternal education is largest at a threshold of 12 years of education.